PENGARUH INTENSITAS DALAM MENGIKUTI UNIT KEGIATAN MAHASISWA, MOTIVASI BELAJAR DAN EFIKASI DIRI TERHADAP PRESTASI BELAJAR MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS SEBELAS MARET ANGKATAN 2015 DAN 2016 - -, Agata Martha Wardani -; -, Bambang Wasito Adi -; -, Sunarto - (Pendidikan Ekonomi Bidang Keahlian Khusus Tata Niaga FKIP Universitas Sebelas Maret, 2018)
This study aims to determine (1) The effect of intensity following the Student Activity Unit, learning motivation and self efficacy together to the achievement of the students of Economic Education class of 2015 and 2016, (2) The influence of the intensity of following the student activities toward the achievement of the students of Economic Education class of 2015 and 2016, (3) Influence of learning motivation to student achievement of Economic Education class of 2015 and 2016, (4) Effect of self efficacy to student achievement of Economic Education class of 2015 and 2016. Object of this research were Student of Economic Education class of 2015 and 2016 which amounted to 127. The population of this research was used to be sample. Data were collected by questionnaire and documentation. Questionnaires were used to collect data on the intensity of Student Activity, learning motivation and self efficacy while documentation was used to collect data for Student Achievement Index. Data were analized by multiple regression analysis. The results of this study are: (1) There is a significant influence between the intensity of following student activity, learning motivation and self efficacy to the achievement of the students of Economic Education class of 2015 and 2016 which is indicated by the value F count greater than F table, that is 60,517> 2.73. (2) There is a significant influence between intensity of student activity on student achievement of Economic Education class of 2015 and 2016 which is shown by t count of intensity variable following student activity is t count equal to 4,434> t table that is 1,993 and sig value. 0,000 <0.05. (3) There is a significant influence between learning motivation on student achievement of Economic Education class of 2015 and 2016 which shown by t count value of learning motivation is 2,441> t table that is 1,993 and sig value. 0,000 <0.05. (4) There is significant influence between self efficacy to student achievement of Economic Education class of 2015 and 2016 which is shown with self efficacy t count value is 5,590> t table that is 1,993 and sig value. 0,000 <0.05.